Study on system dynamics model of network information lifecycle - Qingmin Zhang; Bin Hu (2010 IEEE International Conference on Intelligent Computing and Intelligent Systems, 2010)
As network information is of great instability, its amount may occur surge or speed reduction, and its contents may also occur a qualitative change in a short time, so the study of information lifecycle issue in network environment has caused people's extensive attention. In this paper the main factors of network information's lifecycle evolution include the factor of information subject, web link rate, users' participation rate, social effect rate, users' concern, information type, users' evaluation and utility value. The system dynamics model of the information lifecycle in the network environment is built by using the simulation software Anylogic. It is used to find the general evolution rule of the information lifecycle, which helps people to manage the information effectively. By changing the values of different parameters in the model, the evolution process of the information lifecycle is explored with simulation runs. The different effects of the various parameter values on the information lifecycle is then summarized.